One-year extra-uterine life support for viviparous shark embryos: first technological application to mid-term embryos - Tomita, Taketeru; Toda, Minoru; Kaneko, Atsushi; Murakumo, Kiyomi; Miyamoto, Kei; Sato, Keiichi (Frontiers in Fish Science, 2024)
Shark-specific artificial uterine fluid is a recently developed material suitable for maintaining viviparous shark embryos outside the maternal body. Previous studies confirmed that this fluid greatly extends the captive maintenance period of the embryonic slendertail lantern shark (Etmopterus molleri) from less than one week to several months. Its application, however, has been limited to late-term embryos. This study reports the first application of this fluid on mid-term embryos with long external gill filaments. The incubation was found to be successful, with the embryos growing to their natural birth size after one year. A high mortality of mid-term embryos was observed during incubation due to pressure ulcers. This indicates that not only appropriate chemical environment but also appropriate physical environment is critical for the stable maintenance of midterm embryos.